Paretic complications of tick-borne encephalitis and Lyme neuroborreliosis in the Czech Republic: Characteristics and clinical outcome - Smíšková, Dita; Pícha, Dušan; Slížek, Martin; Džupová, Olga (Ticks and tick-borne diseases, 2024)
Tick-borne encephalitis (TBE) and Lyme neuroborreliosis (LNB), the most common tick-borne diseases of the central nervous system in Central Europe, are frequently associated with pareses. The aim of this study was to characterise paretic complications in patients with TBE and LNB, including their severity, persistence and impact on the patients' quality of life. Our retrospective observational study included patients with aseptic CNS infection due to TBE virus or Borrelia burgdorferi sensu lato. Paretic complications were evaluated in the acute phase and the patients were followed up until complete regression or long-term stabilisation of any neurological deficit. The severity of the neurological deficit was graded according to the modified Rankin Scale (mRS). A total of 823 patients (582 with TBE, 241 with LNB) was included. Paretic complications were diagnosed in 63 TBE patients (10.8 %) and in 147 LNB patients (61.0 %). In TBE, the most common neurological deficit was brachial plexus paresis in 21 patients (33 %) and bulbar symptoms in 18 patients (29 %). In LNB patients, facial nerve palsy was the most frequent neurological deficit (117patients; 79.6 %), followed by lower limb paresis in 23 patients (15.6 %). Forty-nine TBE patients and 134 LNB paretic patients completed follow-up. Paresis resolved within 3 weeks in 16 TBE patients (33 %) and 53 LNB patients (39.5 %), but the proportion of patients with paresis persisting for more than 12 months was significantly higher in TBE (34.7 vs. 3.7 %, p < 0.001). The mean mRS was significantly higher in TBE paretic patients compared to LNB (p < 0.001). Paretic complications are significantly more common in LNB than in TBE but pareses associated with TBE last longer than in LNB and considerably reduce the quality of life of patients. Prevention remains the only way to influence the long-term motor deficits of TBE.
Keywords: lymská neuroborelióza; klíšťová encefalitida; Encephalitis, Tick-Borne; Tick-borne encephalitis; Lyme neuroborreliosis; Humans; Quality of Life; Paresis; Long-term deficit; Lyme Neuroborreliosis; paréza; Czech Republic; kvalita života; lidé; Česká republika